Tool from Pack Carburized Low Carbon Steel - Arianto Leman Soemawidagdo; Tiwan Tiwan; Mujiyono Mujiyono (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2014)
The research is aimed at developing alternative tool from pack carburized low carbon steel. The tools were made from low carbon steel of 111,67 VHN using cutting machine and then sharpened. Carburizing process was conducted at temperature vary of 800, 850 and 900 0C for 1, 2 and 3 hours and then quenched into water and oil. The tools were subsequently quenched after diffusion process. The tools was used to cut mild steel of Ø31,75 mm on EMCO Maximat V-13 lathe machine with cutting speed 25m/minutes, feeding 0,112mm/ rpm and depth of cut 1 mm. Tools that carburized at 850 0C for 3 hours dan quenched in water gives mean maximum hardness of 760,4 VHN and tool life up to 425 second. It shows that the tool is not economical developed for mass production.